Treatment of midshaft clavicle fracture with anatomical contoured clavicular locking plate - Onta, Pratyenta Raj; Sapkota, Krishna; Wahegaonkar, Krishna; Ranjeet, Niraj; Thapa, Pabin; Thapa, Upendra Jung (Asian Journal of Medical Sciences, 2018)
Background: Fracture clavicle is a common fracture around the shoulder joint accounting about 2.6% of all fracture and 44% in shoulder region. Mid shaft clavicle fracture accounts about 81% of total clavicle fracture. Open reduction and plate fixation is a good treatment method for displaced mid shaft clavicle fracture with benefit of early pain free movement of shoulder joint and early return to work. The anatomical contoured clavicular plate maintains mechanical strength and has less soft tissue complications. Aims and Objective: The aim of the study was to evaluate the clinical and radiological outcome, time for fracture union and complications in midshaft clavicle fracture managed with anatomical contoured clavicular locking plate. Material and Methods: This study was done in Manipal Teaching Hospital, Pokhara, Nepal.There were a total of 30 patients (19 male and 11 female) who had displaced mid shaft fracture. All patients underwent plate osteosynthesis with anatomical contoured locking plate. The patients were followed up at 3 weeks, 6 weeks, 3 month and 6 months’ time. Results: There were 30 patients among whom; one patient had bilateral clavicle fracture. The mean age of the patient was 37.19 (11.96) years. The mean time for clinical and radiological union was 8.77 (1.17) weeks and 17.03 (3.06) weeks. All patients in our study had union of fracture with only one patient having superficial surgical site infection. Conclusion: Open reduction and plate fixation is a good option for displaced mid shaft clavicle fracture which help the patient for early pain-free movement of shoulder. Use of anatomical contoured clavicle plate provides fixation of clavicle to its normal contour and provides better fixation and stability.